Elevated pulsatility index of the superior mesenteric artery indicated prolonged mechanical ventilation in patients after cardiac valve surgery - Zhou, Yuankai; He, Huaiwu; Cui, Na; Wang, Xiaoting; Long, Yun; Liu, Dawei (Frontiers in Surgery, 2023)
Purpose This study examined whether alterations in Doppler parameters of superior mesenteric artery (SMA) are associated with prolonged mechanical ventilation (PMV) in patients who underwent cardiac valve surgery. Methods Hemodynamic and SMA Doppler parameters were collected at intensive care unit(ICU) admission. The duration of mechanical ventilation was monitored. PMV was defined as mechanical ventilation ≥96 h. Results A total of 132 patients admitted to ICU after cardiac valve surgery were evaluated for enrollment, of whom 105 were included. Patients were assigned to the control (n = 63) and PMV (n = 42) groups according to the mechanical ventilation duration. The pulsatility index(SMA-PI) and resistive index of SMA (SMA-RI) were 3.97 ± 0.77 and 0.88 (0.84–0.90) in the PMV group after cardiac valve surgery, which was lower than the SMA-PI (2.95 ± 0.71, p < 0.0001) and SMA-RI of controls (0.8, 0.77–0.88, p < 0.0001). SMA-PI at admission had favorable prognostic significance for PMV (AUC = 0.837, p < 0.0001). Conclusions An elevated SMA-PI is common in patients after cardiac valve surgery with PMV. Increased SMA-PI could help predict PMV after cardiac valve surgery. Using point-of-care ultrasound to measure SMA-PI at ICU admission is an acceptable and reproducible method for identifying patients with PMV.